Human Immunodeficiency Virus/Human Papillomavirus co-infection and host molecular genetics of cervical carcinoma - Chambuso, Ramadhani Salum (Department of Pathology, 2020)
A subgroup of women who are co-infected with human immunodeficiency virus type 1 (HIV1) and human papillomavirus (HPV) progress relatively rapidly to cervical disease regardless of the number of absolute CD4 count. During infection, viral peptides are recognized by the host immune system. It is reasonable to propose that the development of viral-associated cancers, like cervical cancer, requires interference with specific immune-response genes. This thesis investigates this proposition with consideration of host molecular genetic alterations and variations of the human leukocyte antigen class II (HLA II) genes as one of the groups of immune-response genes that are involved in directing CD4 T-cell responses during infection, in the instance of cervical cancer progression in HIV-1/HPV co-infected women. Study I, reviewed the available literature on host molecular genetics and HIV-1/HPV coinfection on cervical cancer progression. This study suggests that the dual pro-oncogenic effects of HPV oncoproteins E6/E7 and the HIV-1 oncoprotein Tat, may exacerbate and accelerate the rate of cervical disease progression in a subgroup of HIV-1-positive women. Additionally, HIV-1-positive cervical cancer has three important carcinogenesis steps: firstly, HPV integration into the host genome, secondly, dual pro-oncogenic effects of HPV oncoproteins E6/E7, and the HIV-1 Tat oncoprotein in the host genome and, thirdly, the accumulation of repeated, unrepaired genetic mutations and genetic alterations within the host chromosomal DNA. Genetic variations or mutations that affect the following host gene categories were suggested to be responsible for cervical cancer susceptibility and disease progression; (i) genes for the immune-response against oncogenic HPV infection, (ii) oncogenes, (iii) tumour-suppressor genes, (iv) apoptosis-related genes, (v) DNA damagerepair genes, and (vi) cell cycle-regulatory genes. However, studies II, III and IV are linked together and listed according to the specific objectives of this thesis. Study II, characterized the distribution of HPV genotypes within cervical tumour biopsies from a cohort of 181 HPV-unvaccinated South African women and studied the relationships with HIV-1 infection, age of patients, absolute CD4 count, CD4 percentage and the stage of cervical disease, and identified the predictive power of these variables for cervical disease stage. Distribution of HPV genotypes was related to the stage of cervical disease in HIV-1-positive women. Older age was a significant predictor for invasive cervical cancer (ICC) in both HIV-1-seronegative (p<0.0001) ) and HIV1-positive women (p=0.0003, q=0.0003). Sixty-eight percent (59/87) of HIV-1-positive women with different stages of cervical disease presented with CD4 percentage below or equal to 28 and a median absolute CD4 count of 400 cells/µl (IQR 300-500 cells/µl). Of the HIV-1-positive women, 75% (30/40) with ICC, possessed ≤28% CD4 cells versus 25% (10/40) who possessed >28% CD4 cells (both p< 0.001, q<0.001). Furthermore, 70% (28/40) of women with ICC possessed absolute CD4 count >350 cells/µl compared to 30% (12/40) who possessed absolute CD4 count ≤ 350 cells/µl (both p< 0.001, q< 0.001). Study III, was the first case-control study to investigate the association of HIV-1/HPV coinfection with specific host HLA II-DRB1 and -DQB1 alleles in cervical cancer. Two hundred and fifty-six (256) women of the same ethnicity were recruited, comprising 56 cases and 200 age-matched controls. A total of 624 HLA-DRB1 and -DQB1 class II genotypes were studied. HLA II-DQB1*03:01 and -DQB1*06:02 alleles were associated with cervical cancer in HIV-1/HPV co-infected women (p=0.001 and p< 0.0001, respectively) while HLA II-DRB1*13:01 and -DQB1*03:19 were rare or absent in women with cervical disease when compared to the control population (p=0.012 and 0.011, respectively). Study IV, aimed to investigate the host genetic alterations that may be involved in rapid tumour progression in HIV-1/HPV co-infected women. The frequency of loss of heterozygosity (LOH) and microsatellite instability (MSI) at the HLA II locus on chromosome 6p was analysed in cervical tumour biopsy DNA, with regard to HIV-1/HPV co-infection in 164 women. Seventy-four women were HIV-1-positive and ninety women were HIV-1-seronegative. Tumour DNA from HIV-1/HPV co-infected women demonstrated a higher frequency of LOH/MSI at the HLA II locus at 6p21.21 than tumour DNA from HIV1-seronegative women (D6S2447, 74.2% versus 42.6%; p=0.001, q=0.003), D6S2881 at 6p21.31 (78.3% versus 42.9%; p=0.002, q=0.004), D6S1666 at 6p21.32 (79% versus 57.1%; p=0.035, q=0.052), and D6S2746, at 6p21.33 (64.3% versus 29.4%; p< 0.001, q< 0.001), respectively. This thesis provides novel insights and adds to the existing knowledge on the relationships between HIV-1/HPV co-infection, CD4 immune status, host HLA II allele variations and genetic alterations at chromosome 6p in association or likely protection to cervical disease in the studied cohort of South African women. Identification of host molecular genetic susceptibility to disease with regard to viral infection is important for individualized molecular targeted prevention of cervical cancer.